Female Migration: A Way out of Discrimination? - Ilse Ruyssen; Sara Salomone (Center for Economic Studies and ifo Institute (CESifo), 2015)
In light of the recent feminization of migration, we empirically explore to what extent worldwide female migration can be explained by perceived gender discrimination. Thanks to unique individual level data, we track women's willingness and preparation to emigrate from 150 countries between 2009-2013 and disentangle how perceived gender discrimination can foster or impede female emigration across countries. Our empirical strategy accounts for country of origin fixed effects and is robust to both sample selection bias and potential endogeneity issues. Perceived gender discrimination is shown to form a strong and highly robust incentive to emigrate. Yet, whether those migration aspirations are turned into actual preparations is determined by more traditional push factors such as household income or network effects and constraints such as family obligations. In very poor (sub-Saharan African) countries, however, perceived gender discrimination acts as an obstacle, preventing women from actually moving abroad. This paper presents research output of the Ifo Center of Excellence for Migration and Integration Research (CEMIR)
Keywords: F22; J16; C35; Z10; 330; female migration; gender discrimination; migration desire; conditional logit model